(untitled) (Economics and region, 2022)
Today, ensuring financial stability is a key condition for Ukraine’s sustainable economic development. In the conditions of high risks of the crisis period, the war in Ukraine, the efforts of the government and business entities are focused on solving current problems. Stabilization of the key parameters of the financial system makes it possible to transition to the implementation of the strategic goals of domestic enterprises, which directly affects the financial stability of the country as a whole. The state of the economy of any country is dependent on the level of development of its production sphere. Therefore, the stable development of domestic enterprises is one of the first prerequisites for ensuring a powerful economic system of the state. Their operation is always accompanied by the emergence of a large number of threats that can create a financially dangerous situation. Securing the enterprise, creating the so-called "immunity" to both external and internal threats, which consists, first of all, in the correct, adequate management situation, is one of the main tasks of the enterprise’s financial security management system.